Biocompatibilidade e biodegradação de colágeno, nanoqueratina e bioapatita derivados da indústria avícola - Souza, Francisco Fabio Pereira de (2018)
The use of by-products of the poultry industry for development of biomaterials arouse biotechnology interest to the natural, biomimetic, biocompatible and bioreabsorbable graft production for application in tissue repair. The aim of this study was to evaluate in vivo the biocompatibility and biodegradation of collagen, nanokeratin and bioapatite from poultry byproducts through the quantification of local inflammatory and repair biological responses. Forty-five Swiss mice with 6 weeks of birth received individually two grafts in subcutaneous tissue, one corresponding to the test material, poultry collagen (G1), nanoqueratina poultry (G2) or poultry bioapatite (G3), and the other to the positive control, commercial collagen (G4) or commercial mineralized bone (G5). Descriptive and semi-quantitative histopathological analysis in experimental times of 1, 3 and 9 weeks allowed the determination of inflammatory response, repair and graft integrity. Intergroups statistical analysis of non parametrical data (Kruskal-Wallis test and Dunn post-test) considered significant differences if p<0.05. G1 exhibited upper intensity of neutrophils, macrophages and neovascularization at 1 week, lymphocytes at 1 and 3 weeks and connective tissue in every week and lower presence of graft in every week. G2 exhibited upper intensity of neutrophils, lymphocytes and macrophages at 1 week and foreign-body giant multinuclear cells at 9 weeks and lower presence of graft in every week. G3 exhibited upper intensity of neutrophils at 1 week and macrophages at 1 and 3 weeks and lower presence of graft at 1 week. In conclusion, all materials presented biocompatibility verified by reduction in inflammation and increase of repair and total (collagen and nanokeratin) or partial (bioapatite) biodegradation throughout the experiment. Based on their biological characteristics, collagen and nanokeratin-based materials exhibit potential for biotechnological development as hemostatic agents for the treatment of small bone defects, while bioapatite exhibits potential as a bone graft for the treatment of bone loss from small to moderate.